Decision Development of Constitutional Court on Heritage Rights of Children Outside of Marriage - Devi Sumiwardani (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
Based on Islamic law and the Civil Code, children who born outside of marriage have a different status with legitimate children. This difference is due to the validity of the marriage relationship. It seems that the issue of children outside of marriage in Indonesia is still being questioned by people, even though conceptually or in formal juridical terms there are legal provisions regulating it. In society and the law, confusion often occurs due to differences in legal rules. The issues that will be discussed in this research are; (1) How is the implementation of the inheritance rights of children outside of marriage according to positive law in Indonesia? (2) How are legal protection measures for children outside of marriage? and (3) What is the legal consequence of the Constitutional Court Decision which is seen as a development towards the inheritance rights of children outside of marriage? This research uses a normative juridical approach that analyzes articles in statutory regulations. The research specification is descriptive analytical, which aims to provide a detailed, systematic and comprehensive description of the civil rights issues of children outside of marriage. The data collection method uses primary legal materials consisting of books and opinions of scholars and various laws and regulations and secondary legal materials consisting of internet sites. The conclusion of this study is that children outside of marriage have legal consequences, namely the consequences of having the right to legal recognition and protection if they fulfill Article 2 paragraph (2) of Act No. 1 of 1974. The Constitutional Court's decision is of the opinion of Article 43 paragraph (1) of Act No. 1 of 1974 that “children who born outside of marriage only have a civil relationship with their mother and their mother's family, as well as men as their father, which can be proven based on science and / or other evidence by law to have blood relations including civil relations with their father's family. The Constitutional Court decision only concerns children resulting from marriage who are not registered, not children resulting from adultery. Regarding the result of adultery children who do not have a family relationship, marriage guardian, inheritance and income from the male who caused the birth.